PENGARUH SELEKSI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. BHAKTI SHARE REGISTRAR - Tini Juartini (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
This study aims to determine the effect of selection and training on the performance of employees of PT. Bhakti Share Registrar. This type of research is a type of quantitative research using survey methods and data collection. In this study, researchers used a questionnaire in the form of written questions given to respondents and distributed to all employees of PT Bhakti Share Registrar. Data collection techniques through the distribution of questionnaires. The results of the study show that: both in a simple and multiple way there is a positive and significant effect of selection and training on the performance of employees of PT. Bhakti Share Registrar.